Consumer’s Adoption of Last Mile Logistics Innovation: A Systematic Literature Review - Muhammad Iqbal Firdaus (Institut Transportasi dan Logistik Trisakti, 2023)
Last mile logistics refers to the final stage of the delivery process where products are transported from a distribution center to the end customer. In recent years, advancements in technology and changes in consumer behavior have led to an increased focus on last mile logistics. However, last mile logistics pose challenges due to its complexity and uncertainty affecting both the firms or logistics service providers and the customers. Studies focusing on achieving efficient last mile logistics have gained attention from scholars while research discussing factors affecting customer’s adoption on last mile logistics innovation remain scant. This conceptual paper aims to explore the factors that influence customer adoption of last mile logistics through a systematic literature review of selected 21 papers from reputable journals. The papers were analyzed and resulted in three broad categories of perspectives discussing factors considered by customers to adopt last mile logistics innovation. Future studies are recommended to address issues not covered in this study.